Strategic management for purchases: application of the abc curve and kraljic matrix determining an ideal order model - Bastos, Lucas Matheus Fonseca; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2021)
Given the commercial difficulties experienced between wholesalers in the dispute for prices, partnerships and trust, for companies seeking to stand out, it is necessary to start a sectorial organization work and explore possibilities of applying a competitive differential to stand out among direct competitors. In this way, with good strategic management, the company is able to establish itself and can be assertive in decision-making, supplier selection and adequacy in the acquisition of supplies. Based on this, this study aims to develop an adequate stock replenishment condition for the "pipes" product group registered in the company, which will be classified based on the level of importance and financial impact, and should adjust the acquisition quantities within the constraints established using targeted tools. These being the ABC Curve, which classifies the main items of the group by the level of importance and financial framework, directly impacting the company, and the Kraljic Matrix, which correlates the items with their storage and financial risks, directing strategies and assisting the buyer in decision making. Thus developing an ideal monthly order model, following the established restrictions and reducing the levels of stockouts. It can also serve as a structural pillar for further analysis, directions in this field and future research.